Impact Of Clinical Simulation On The Learning Of Technical Skills In Health Professionals (The Review of Diabetic Studies, 2025)
Clinical simulation has emerged as a vital tool in the education of health professionals, transforming the way in which technical skills are acquired and honed. Objective: to determine the effectiveness of clinical simulation in improving technical competencies and student satisfaction. A quantitative approach was used, applying a structured survey with a validated questionnaire based on the Likert Scale, the sample included 81 students from the Faculty of Health of the State University of the South of Manabí. Cronbach's alpha was calculated, obtaining a coefficient of 0.99, which indicates high reliability in the items evaluated. The results showed that 42% of the participants considered their simulation experience as satisfactory, and 30% recognized improvements in their technical skills. However, 34% were neutral regarding these advances. Concluding that clinical simulation is positively valued by many students, there are areas for improvement, especially in the connection between theory and practice.